Association between bruxism and screen time in adolescents: exploratory study (Research, Society and Development, 2021)
Adolescents make constant use of technologies, which can lead to overuse of the screen. These in turn generate mental consequences, such as stress and anxiety, which are triggering factors of bruxism. Considering this, this cross-sectional study aimed to analyze the association between bruxism and screen time in 236 adolescents, aged between 14 and 19 years of both sexes, high school students from public schools. Data were collected through questions contained in the National School Health Survey (PeNSE), Youth Risk Behavior Survey (YRBS) and Diagnostic Criteria for Research in Temporomandibular Dysfunction (RDC/TMD). The Chi-Square test was used, and the Prevalence Ratio (PR) was calculated. Among the surveyed, 30.9% were bruxists and 62.3% used screens excessively. As for bruxism, there was no association with the independent variables studied. In relation to screen time, "Monthly family income" showed an association (p-value of 0.008), in which 76.1% of the surveyed who used screens for more than two hours a day had a monthly income between one and two minimum wages. Thus, there was no association between bruxism and screen time in adolescents. Bruxism and screen time were also not associated with the variables gender and age, however, there was an association between screen time and family income.